Sosialisasi Pengaruh Lingkungan Sekolah terhadap Proses Pembelajaran Peserta Didik - Donal Donal; Dinda Mayana; Masna Ayu Lumban Toruan; Nikita Putri Marsanda S; Dwi Dara Yonita; Firda Nur’aini; Uthia Tri Andani; Nurul Azizah (Karya Nyata : Jurnal Pengabdian kepada Masyarakat, 2024)
This research examines the influence of the school environment on students' learning processes within the context of educational psychology. The school environment, including physical factors such as noise, lighting, and classroom conditions, as well as social factors like student-teacher interactions, significantly impacts the quality of learning. These factors can affect students' concentration, motivation, and academic performance. In educational psychology, a conducive environment has been proven to support effective learning and improve educational outcomes. This study aims to identify school environment aspects that influence the learning process and provide recommendations for creating optimal conditions for both academic and psychological development of students.